Universal platform for functional testing of printed circuit boards. (26th March 2015) - Serban, Marian; Vagapov, Yuriy; Holme, Reg
The paper presents the development of a cost-effective, universal platform for testing of printed circuit boards (PCBs) at the function level. The platform architecture is based on the set of PXI compatible instruments operating under National Instrument software. The system can be easily reconfigured and reprogrammed to minimise the test time and expand test coverage. Comparing to existing functional testing equipment aimed to test one particular PCB only, the proposed platform is universal and designed to test a variety of PCB circuits. This approach reduces the test time and the cost of testing equipment and consequently overall cost of the end product.